2014
DOI: 10.1111/bjc.12068
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotion regulation on social participation following stroke

Abstract: This research highlights the following important clinical implications: Following a stroke, emotion regulation can be immediately and persistently affected, with post-stroke individuals experiencing greater difficulties with their emotion regulation than control participants. Emotion regulation can significantly predict important stroke outcomes including social participation and quality of life, over and above physical limitations and other post-stroke confounders. This study highlights the potential for deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 45 publications
1
24
0
2
Order By: Relevance
“…For deficits in emotion regulation, the same consequences have been established [45]. The patient's spouse reported that the patient showed slight irritability and slowness in communication after the stroke, although the patient himself stated having no difficulties in social interaction.…”
Section: Discussionmentioning
confidence: 80%
“…For deficits in emotion regulation, the same consequences have been established [45]. The patient's spouse reported that the patient showed slight irritability and slowness in communication after the stroke, although the patient himself stated having no difficulties in social interaction.…”
Section: Discussionmentioning
confidence: 80%
“…Deficits in this area have been associated with callous affect (Zeigler‐Hill & Vonk, ) and are therefore unlikely to positively contribute to relationship satisfaction. Additionally, Cooper and her colleagues (), who were studying stroke patients, found a relation between a greater lack of emotional awareness and dissatisfaction in close relationships.…”
Section: This Studymentioning
confidence: 98%
“…On the other hand, there is relatively little attention to the social recovery of patients. Support for social recovery may include professional support to return to work, access social benefits, participate in activities of daily life, maintain contact with family and friends and organize financial affairs [21][22][23]. According to the "Burden of stroke in Europe" report there is a lack of long-term support (that we term "aftercare") for stroke in every European country [24].…”
Section: Introductionmentioning
confidence: 99%